Persepsi Mahasiswa Tentang Faktor Kesulitan Mempelajari Kanji - Halibanon, Dewi Saparina; Dirgandini, Melinda; Faiz Khoerul Musyaafa, Muhammad; Mulyawan Setiana, Soni (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 7 No 1 (2025)DO - 10.24843/JS.2025.v07.i01.p08, 2025)
This study aims to determine the problems of kanji learning difficulties and how to overcome them at three private universities in Bandung, namely Universitas Nasional Pasim, Universitas Kristen Maran a tha, and Universitas Komputer Indonesia involving 125 students. The method used in this study is a quantitative descriptive method by distributing questionnaires to students as a research instrument via Google Forms. Then the data is processed in the form of a percentage to find students' responses or perceptions of the difficulties in learning kanji and efforts to overcome them. From the results of the study, it was found that third-semester students of the Japanese Literature Study Program from three private universities in Bandung had difficulty mastering basic kanji. The difficulties experienced by students in sequence were difficulty in understanding the meaning of kanji, difficulty in writing kanji, difficulty in understanding the number of kanji strokes, difficulty in understanding bushu, and difficulty in reading kanji. To overcome these difficulties, students prefer to ask lecturers outside of class hours and use the internet to learn kanji. However, not many students learn kanji independently. Therefore, to improve students' ability to master kanji, the use of collaborative learning methods or project-based learning is required.